ANALISIS KINERJA KEUANGAN PERBANKAN SYARIAH INDONESIA PADA MASA PANDEMI COVID-19 - Sri Diana; Sulastiningsih Sulastiningsih; Purwati Purwati (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
Financial sector is an important thing for a country development. Indirectly, the financial sector will support the economy especially during the pandemic, including the Islamic banking industry. This study aims to analyze the financial performance of Islamic banking in Indonesia based on profitability ratios consisting of BOPO, ROA, ROE, liquidity ratios consisting of Cash ratio and FDR, as well as solvency ratios as measured by the CAR ratio, during the COVID-19 pandemic. This research is descriptive quantitative research by measuring the financial performance of the bank through the level of profitability ratios. The results of this study show that there is a fluctuation changing in the performance values during the COVID-19 pandemic. Bank performance through profitability ratios shows that some sharia banks are classified as efficient and some have decreased the performance. In the liquidity ratio, the average bank experienced a decline in the cash ratio component, with the lowest being at BRI Syariah, which fell by 50.9%. Bank solvency ratio generally shows good performance.